The effect of the Anticipation Guide strategy on the achievement of history for fourth-grade literary students (Journal of Imam Al-Kadhim College, 2023)
Abstract:The research aims: to know the effect of the "Anticipation Guide strategy" on the achievement of history for fourth-grade students of middle school.The researcher: used the experimental desìgn with partial control with the post achievement test.Division –A- of the fourth literary grade, "Al-Thawra Preparatory School" for Boys, was determined to represent the experimental group: that is taught according to the "Anticipation Guide strategy", and Division –B- represented the control group that studies the traditional teaching method. The number of students was -70- students, with -35- students in each Collection. The two groups were rewarded in the variables: chronological age, intelligence. The researcher prepared the research tool, the achievement test, and the validity and reliability of the tool were verified. The :-T-test- test was used to process the data:, and the results showed the superiority of the experimental group that was studied according to the Anticipation Guide strategy in achievement, and the researchers recommended using the wave prediction strategy in teaching.
Keywords: Anticipation Guide strategy, traditional teaching method, wave prediction